Research progress in treatment of severe acute pancreatitis by regulating gut microbiota with traditional Chinese medicine - Xin Yang (Editorial Board of Journal of Hainan Medical University, 2021)
In recent years, it has been shown that the late development of severe acute pancreatitis is often accompanied by gut microbiota dysbiosis, leading to an increase of pancreatic necrosis and peripancreatic infection. Basic western medicine such as antibiotics can prevent infection but may disrupt the balance of gut microbiota.1As a treasure of traditional Chinese medicine, which has become one of the complementary and alternative therapy for gut microbiota disorder in severe acute pancreatitis. This article reviews the treatment of severe acute pancreatitis by regulating gut microbiota in multiple ways with traditional Chinese medicine, which would provide new approaches and ideas for clinical treatment of severe acute pancreatitis.